THANK YOU FOR ALERTING ME TO THE PROPOSAL BY THE GENERAL SERVICES ADMINISTRATION TO RESTRICT SMOKING IN ALL FEDERAL BUILDINGS. (Tufts Archival Research Center, 2007)
Copy; Copy of mass-distributed response postcard initially sent from RJR Action Alert and returned by Robert Bradley. Indicates Mr. Bradley has filed a written complaint with the General Services Administration protesting proposed smoking restrictions in federal buildings.